A special place in the saltings? Survey and excavation of an Iron Age estuarine islet at An Dunan, Lewis, Western Isles - Church, Mike J; Nesbitt, Claire; Gilmour, Simon M D (Proceedings of the Society of Antiquaries of Scotland, 2014)
This is the third of a series of four papers that present the excavations undertaken on the Uig peninsula, Isle of Lewis, as part of the Uig Landscape Project. We present the archaeological evidence from An Dunan, a causewayed tidal islet in the salt marsh of Uig sands, a liminal and potentially ritual site dating to the Iron Age and medieval period. The first main Middle Iron Age phase was characterised by activities centred on an ash mound, demarcated by four large orthostats, within an essentially rectilinear structure containing internal cellular divisions. The activities within the structure have been interpreted as non-domestic in nature. The second main phase involved the medieval re-use of aspects of the Iron Age building to create a small boat-shaped structure, with very little associated material culture. The structural, artefactual and environmental evidence from the site is presented, before being interpreted within the wider research context of the archaeology of the Western Isles and Atlantic Scotland.